A non-linear relationship between lesion length and risk of recurrent cerebral ischemia after stenting for symptomatic intracranial stenosis with hemodynamic impairment - Zhang, Xianjun; Gong, Wentao; Meng, Zhen; Li, Guangwen; Liu, Peng; Zhang, Yong; Wang, Naidong (Frontiers in Neurology, 2023)
Background Stent placement can be an effective treatment for patients with symptomatic intracranial stenosis (sICAS) and hemodynamic impairment (HI). However, the association between lesion length and the risk of recurrent cerebral ischemia (RCI) after stenting remains controversial. Exploring this association can help predict patients at higher risk for RCI and develop individualized follow-up schedules. Method In this study, we provided a post-hoc analysis of a prospective, multicenter registry study on stenting for sICAS with HI in China. Demographics, vascular risk factors, clinical variables, lesions, and procedure-specific variables were recorded. RCI includes ischemic stroke and transient ischemic attack (TIA), from month 1 after stenting to the end of the follow-up period. Smoothing curve fitting and segmented Cox regression analysis were used to analyze the threshold effect between lesion length and RCI in the overall group and subgroups of the stent type. Results The non-linear relationship between lesion length and RCI was observed in the overall population and subgroups; however, the non-linear relationship differed by subgroup of stent type. In the balloon-expandable stent (BES) subgroup, the risk of RCI increased 2.17-fold and 3.17-fold for each 1-mm increase in the lesion length when the lesion length was <7.70 mm and >9.00 mm, respectively. In the self-expanding stent (SES) subgroup, the risk of RCI increased 1.83-fold for each 1-mm increase in the lesion length when the length was <9.00 mm. Nevertheless, the risk of RCI did not increase with the length when the lesion length was >9.00mm. Conclusion A non-linear relationship exists between lesion length and RCI after stenting for sICAS with HI. The lesion length increases the overall risk of RCI for BES and for SES when the length was <9.00 mm, while no significant relationship was found when the length was >9.00 mm for SES.